Factors a ecting work environment at Westchester Community College in New York - Gutiérrez, Karla Saraí; Howson, Doreen R. (Anuario de Investigación UM, 2020)
The empirical model in which work training, work motivation, leadership and communication are predictors of work environment, as perceived by employees of Westchester Community College in New York, USA.